Uso da medicação homeopática no tratamento da ceratoconjuntivite primaveril em crianças entre 3 e 10 anos - Claudio Maciel de Sena (2014)
Objective: To compare the efficacy between the homeopathic and hallopathic treatments of vernal keratoconjunctivitis (VKC) in children. Methods: Study design: prospective, 1-year, double blind, interventional. Thirty six patients, between 3 and 10 years of age, with VKC were assigned in two groups to receive medical treatment, the homeopathic group (HG) with 19 patients (18 male, 1 female), and the allopathic group (AG) with 17 patients(10 male, 7 female). A sample data collection form for symptoms (itching, pain, foreign body sensation, photophobia, tearing, interference in the day-to-day) and bibmicroscopic signs (hyperemia, papillary hypertrophy, epithelial erosions punctate, Horner-Trantas dots, mucous secretion, limbal vernal) were used. Intervention: Each patient of homeopathic group received two eye-drops containing 1 mg dextran 70, 3mg hypromellose, and polyquad (preservative), a capsule with 500mg of lactose, and two drops of homeopathic medicine. The homeopathic medicines have been chosen as the individualizing symptomatic totality of each patient, and taught in centesimal hahnemannian scale. Each patient of allopathic group received a vial containing dexamethasone 0,1%, a vial with disodium cromoglycate 4%, and a capsule containing 500mg of lactose. Statistical analysis: the multivariate statistical technique called principal components analysis, the model of generalized estimating equations or marginal model, and the Student's t test. Results: The vernal conjunctivitis of the mixed type was the most frequent (47% in AG, 53% in HG). The allopathic and homeopathic treatment alleviated the symptoms with regression of signs, and no adverse effects were detected. First, homeopathic treatment promoted symptoms relief, and then reduced the signs. Conclusion: A single dose of homeopathic treatment was effective in relieving symptoms and reducing signs of vernal keratoconjunctivitis.